PUBLIC-PRIVATE PARTNERSHIP IN UKRAINE: DEVELOPMENT PROSPECTS AND IMPACT ON INFRASTRUCTURE REHABILITATION - Petrukha, Nina (Public Management and Policy, 2024)
<span lang="EN-US" style="font-size: 10.0pt; line-height: 107%; font-family: 'Cambria',serif; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-font-weight: bold; mso-bidi-font-style: italic;">In Ukraine, the war has increased the need for urgent infrastructure restoration. Destroyed facilities need to be modernized for the stability of the economy. Public-private partnerships effectively attract investments by mobilizing resources and distributing risks, which increases management efficiency. However, the implementation of public-private partnerships faces challenges, such as an imperfect regulatory framework and corruption, which need to be addressed for further development. The purpose of the study is to explore the possibilities of developing public-private partnerships in Ukraine, taking into account the socio-economic context and the needs of the population. The object of the study is the mechanisms of interaction between the public and private sectors and their impact on the restoration of Ukraine’s infrastructure. The study is based on scientific works, statistical data and regulations. Methods used: morphological, empirical, statistical, analysis and synthesis, structural and logical analysis. Theoretical approaches to the interpretation of the concepts of “public-private partnership” and “public-private partnership” are generalized, and common and distinctive features are outlined. The peculiarities of the legislative and regulatory framework of public-private partnership in Ukraine are determined. The key advantages and disadvantages of the legislative and regulatory framework for public-private partnerships in Ukraine are outlined. The main indicators of economic development of public-private partnerships in Ukraine for 1990-2023 are presented. The main stages of public-private partnership formation in the time period of 2015-2024 are identified and characterized. The study recommends the main factors of impact of public-private partnerships for the restoration of Ukraine’s infrastructure, including attracting private investment, effective project management, risk sharing, innovation, job creation, improving the quality of services, and attracting international partners.